Real-world referral pattern and outcomes of diabetic patients who undergo revascularization: data from the prospective Multi-vessel Coronary Artery Disease (MULTICAD) Israeli Registry. (25th February 2019) - Ram, Eilon; Goldenberg, Ilan; Sternik, Leonid; Peled, Yael; Segev, Amit; Kogan, Alexander; Vorobeichik Pechersky, Dina; Shlomo, Nir; Raanani, Ehud
Abstract: OBJECTIVES: Diabetes mellitus patients with multivessel coronary artery disease present with a poor prognosis. We aimed to explore real-life clinical outcomes of diabetic patients who were referred for coronary revascularization. METHODS: We used data from the Multi-vessel Coronary Artery Disease (MULTICAD) Israeli Registry. Using descriptive statistics, Kaplan–Meier, Cox and logistic regression, we described a revascularization referral pattern, short-term outcomes and long-term survival among 475 diabetic patients with multivessel and/or left main disease, 48% of whom underwent surgical and 52% percutaneous revascularization. RESULTS: Factors independently associated with referral for surgery included the presence of left main stenosis [odds ratio (OR) 1.89; P  = 0.030] and a higher Syntax score (OR 1.15 per point increment; P  < 0.001), whereas an older age (OR 1.03 per 1-year increment in age; P  = 0.019), prior percutaneous coronary intervention (OR 1.83; P  = 0.009) and the presence of renal impairment (OR 2; P  = 0.026) were associated with percutaneous coronary intervention referral. At 7 months of follow-up, multivariable analysis did not reveal any difference in mortality risk between the surgical and percutaneous revascularization groups [hazard ratio (HR) 1.23, 95% confidence interval (CI) 0.5–3.04; P  = 0.649], whereas after 7 months, surgical revascularization was associated with a significant survival benefit (HR 2.24, 95% CI 1.03–4.87; P  = 0.042). CONCLUSIONS: Our observation suggests that in a real-world setting, only approximately one-half of diabetic patients with multivessel disease are referred to surgical revascularization despite guideline indications. Surgical compared to percutaneous revascularization in this population was associated with improved long-term survival that became evident 7 months after the revascularization procedure.